Customers attitude toward Islamic mobile banking in Indonesia: Implementation of TAM - Alex Fahrur Riza; Muhammad Riza Hafizi (Faculty of Business & Economics, Universitas Islam Indonesia, 2019)
Purpose: This study aims to test consumer acceptance of mobile banking Islamic banks using the Technology Acceptance Model. The concept of mobile banking is used to examine the role of banking in facilitating mobile consumer financial transactions.Methodology: This study uses a survey with a sample of 179 users of mobile banking applications Islamic banks in Central Java and Yogyakarta. Data analysis used in this study is SEM with AMOS software assistanceFindings: All hypotheses are supported. Based on the consumer's perspective, mobile banking is an opportunity for the Islamic finance industry. However, mobile banking will transform very quickly and brought new challenges in the era of industry 4.0.Originality: This study enrich the discussion in the literature by retesting the technology acceptance model (TAM) to explain the usage of mobile banking of Islamic bank.